ANALISIS KINERJA LEMBAGA PENDIDIKAN LP3I SAMARINDA DENGAN PENDEKATAN METODE BALANCED SCORECARD - -, SITI ROHMAH (EKONOMIA, 2017)
In the face of increasingly complex business competition as it is today, educational institutions need performance measurement methods that can assess the performance of agencies accurately and thoroughly. In this case the method that can be used is Balanced Scorecard. So the purpose of this study is to determine the application of Balanced Scorecard on performance at LP3I Institution Samarinda. The purpose of using Balanced Scorecard method is to measure institutional performance from four perspectives, namely: growth and learning perspective, internal business process perspective, customer perspective, and financial perspective. The author performs performance measurement at Lembaga LP3I Samarinda using financial data year 2013-2015 to analyze financial perspective, while for customer perspective, Business Process Internal perspective and perspective Learning and growth using institution data and calculation of questionnaires distributed to Students and employees in year walk. The measurement that has been done, it is known that the performance of Lembaga LP3I Samarinda as a whole has decreased with sufficient category, it is indicated by Scorecard value generated from each perspective. The conclusion that can be taken through the analysis that has been done is that the Balanced Scorecard is the best method in assessing the performance of the institution, because the Balanced Scorecard raises important aspects that are ignored by traditional performance measurement, such as human resources aspect, the system used in Institutions, operational processes, and aspects of customer satisfaction and employee satisfaction, so that the measurement results with the Balanced Scorecard will be more accurate. Accurate performance measurement results are critical to management, both in planning, decision-making, and control processes, and in realizing the institution's vision and mission